PEMANFAATAN MEDIA AUDIO VISUAL DALAM PENGENALAN HURUF HIJAIYAH DI TK BINA 45 II PONTIANAK - Sari, Puspita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractIntroduce letters hijaiyah can use media learning .This is done to motivate children in learning .In kindergarten bina 45 II Pontianak that teachers have used media audio visual in introduce letters hijaiyah .So far the constraint most frequently teachers face like a difficult rank letters hijaiyah , the difficulty distinguish a few letters as خ ح ھ .... ق ك.... ش س ث .With the obstacles still teachers face in introduce letters hijaiyah , this needs to the problem solving to the introduction of letters hijaiyah through media audio visual in a kindergarten bina 45 II Pontianak .Problems this research is. How learning in the use of media audio visual knowledge of letters hijaiyah in the class B2 kindergarten bina 45 II Pontianak ? Research methodology to be used in this research is research descriptive with a qualitative approach .The subject of study is 1 teachers and 20 children .Based on the research done in general can be drawn a conclusion that: 1 planning activities in the use of media audio visual knowledge of letters hijaiyah have did as teachers are categorized good , in addition with the planning who have all the activity pembelajaan may be prepared in systematic of to ease the way learning activities .2 ) presentation weighting in the use of media audio visual knowledge of letters hijaiyah have did as teachers are categorized good, in addition to the implementation of the learning to the use of media audio done can increase a generation of kids able know letters hijaiyah .3 ) of the evaluation learning by using media audio visual the introduction of letters hijaiyah categorized develops very good ( bsb ) , in terms of this child can know letters hijaiyah know the concept of letters and distinguish letters hijaiyah with skilled , in addition the child gets said the letter hijaiyah skilled and eloquently . Keywords: audio visual media , the hijaiyah